Analisis Risiko Kinerja Tenaga Pendidik dalam Era Transformasi Digital di Sekolah - Sarah Georetty Manullang (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The digital transformation in education has brought significant changes to learning systems, school management, and the performance of educators. This study aims to analyze the risks educators face in maintaining and improving their performance in the digital era. These risks include aspects of technology adaptation, workload, digital competence, and teacher psychological well-being. The method used in this study is a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation studies of teachers in several secondary schools. The analysis results indicate that most educators face difficulties in adapting to the demands of educational technology, such as the use of Learning Management Systems (LMS), digital platforms, and interactive learning media. Furthermore, there is a risk of decreased work motivation due to increased digital administrative burdens and a lack of ongoing training. School leadership and organizational support also play a crucial role in mitigating these risks. This study emphasizes the importance of risk management strategies for educator performance through improving digital competencies, strengthening technical and psychological support, and developing policies that adapt to technological change. In conclusion, digital transformation requires not only technical capabilities but also mental readiness and a managerial system that is responsive to the dynamics of change. The results of this study are expected to serve as a basis for policymakers in the education sector to design teacher professional development programs that are more relevant to the challenges of the digital era.